2017
DOI: 10.1097/prs.0000000000003282
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Epidemiology of Breast Implant–Associated Anaplastic Large Cell Lymphoma

Abstract: This study demonstrates a statistically significant association between textured breast implants and breast implant-associated ALCL. Although women with a textured breast implant have a low risk of developing breast implant-associated ALCL, the current U.S. incidence is significantly higher than that of primary ALCL of the breast in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
212
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(230 citation statements)
references
References 29 publications
4
212
0
14
Order By: Relevance
“…The annual incidence of BI‐ALCL is 0.1‐0.3 per 100 000 women who undergo breast reconstruction, (5 cases in 1.7‐5.1 million person‐years) …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The annual incidence of BI‐ALCL is 0.1‐0.3 per 100 000 women who undergo breast reconstruction, (5 cases in 1.7‐5.1 million person‐years) …”
Section: Discussionmentioning
confidence: 87%
“…The estimated incidence of BI‐ALCL is <3 per 1 million person years, approximately 0.1‐0.3 per 100 000 women with prostheses per year …”
Section: Introductionmentioning
confidence: 99%
“…Ten cohort studies were included (McLaughlin 2006, Friis 2006, Pan 2012, Largent 2012, Vase 2013, Wang 2015, Warschkow 2016, Doren 2017, Loch‐Wilkinson 2017, Campanale 2018), which only two were prospective (Largent 2012; Wang 2015). Two case‐control studies were included (de Jong 2008; de Boer 2018) (48, 49), which were complementary and shared part of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…BI‐ALCL is a rare entity, first described by Keech and Creech in 1997 . As the name implies, this is a form of T‐cell lymphoma associated with cosmetics or reconstructive BIs, with an estimated risk of 33 per 1 million per year …”
Section: Previous Cases Of Bi‐alcl With Nodal Involvement Reported Inmentioning
confidence: 99%
“…Usually, implant removal with complete excision of any mass with negative margins and total capsulectomy is the best therapeutic option in those patients with localized disease restricted to the capsule . When BI‐ALCL is confined to the seroma cavity, the prognosis seems to be favourable and chemotherapy does not appear to influence outcome . It has been demonstrated that lymph node involvement (LNI) in BI‐ALCL is very uncommon, usually associated with a reduction of the overall survival as well as event‐free survival.…”
Section: Previous Cases Of Bi‐alcl With Nodal Involvement Reported Inmentioning
confidence: 99%